SPECT/CT in Melanoma Lymphoscintigraphy. (December 2016) - Tew, Khimling; Farlow, David
Abstract : Abstract: Sentinel lymph node biopsy is a crucial part of staging intermediate and thick melanoma. Lymphatic drainage from a tumor site can be highly variable, especially on the head, neck, and trunk. SPECT/CT fuses nuclear medicine and x-ray CT images to produce images with high anatomic detail. At our institution, SPECT/CT is performed routinely in addition to planar imaging. This article presents examples where SPECT/CT has proven helpful in image interpretation.